Strained alkyne polymers capable of SPAAC via ring-opening metathesis polymerization. Issue 38 (16th September 2021) - Vasdev, Rajeshwar; Luo, Wilson; Classen, Kyle; Anghel, Michael; Novoa, Samantha; Workentin, Mark S.; Gilroy, Joe B.
Abstract : We present a strategy that combines the attractive traits of chain-growth polymerization and strain-promoted azide–alkyne cycloaddition chemistry for the production of functional polymers. Abstract : The incorporation of strained alkynes into polymers is generally achieved by employing step-growth polymerization methods or post-polymerization reactions. Here, we demonstrate that cyclopropenone-masked strained alkynes are tolerant to chain-growth ring-opening metathesis polymerization, and that, upon post-polymerization photochemical demasking with loss of CO, the strained alkyne group appended to each repeating unit can be used to prepare functional ( e.g., fluorescent or redox-active) polymers from a common polymer backbone. We support our claims about polymer transformations throughout the manuscript through the inclusion of a complete set of model reactions and characterization data for analogous molecular species. The findings of this study are transferable to other polymeric systems, opening the door to the creation of libraries of multifunctional chain-growth polymers with identical polymer backbones.